Understanding how Victoria, Australia gained control of its second COVID-19 wave - James M. Trauer (Nature Portfolio, 2021)
The state of Victoria, Australia experienced a substantial second wave of COVID-19 but brought it under control with strict non-pharmaceutical interventions. Here, the authors model the second wave in Victoria to estimate the impacts of the different interventions.